A study on the impacts towards the loyalty of the employee among the back of house staffs in hotel industry - Kee, Hui Poo; Low, Pei Wa; Ooi, Chong King; Sam, Man Keong; Teng, Choon Hou (2012)
Research provides result from the fact that it is empirical, rather than merely theorizing about what might be effective or what could work. Hence it is becoming more important in any business organization for it to stay competitive in the market. These studies will able to provide our target: hotel industry in Perak Malaysia an opportunity to scrutinize the determinants of contributing employee loyalty of the back of house staff employee In the hotel industry and analyze and establish strategies in according to the business environment. This study includes four independent variables. Relationship of employee loyalty with the four independent variables will be investigated in this paper. The investigation was done by distributing 160 set of questionnaire to the back of house staff. 30 target respondents will be targeted for pilot test and 160 responses will be collected from the targeted respondents. The questionnaire results show that there is a significant correlation between employee satisfaction and loyalty with the four independent variables. Namely, relationship with supervisor, recognition and rewards, working conditions, teamwork and cooperation shows high correlation with the dependent variable afore mentioned. We’re sincerely hoped that the findings could assist the management in the hotel industries on the subject of hotel management knowledge.